Celal Nuri and His Conceiving of the Prophet Muhammad According to His Book Titled Hatemu’l-Enbiya - Çog, Mehmet (Necmettin Erbakan Üniversitesi, 2006)
II. Constitutional Period is a very important era in which new ideas effecting the social and cultural life of the Ottomans appeared. One of these is mentality change appeared in the historiagraphy. Tarih-i Osmani Encümeni that was established in this period had an influnce on the beginning of scientific historiography in or country. Celal Nuri had contributed to this area with his ideas in his siyer. In Hatemu’l-Enbiya, he mainly discusses how the Siyer books to be written and how the Prophet Muhammad to be concieved. In doing so, he evaulates the social and human aspects of the Prophet Muhammad such as his character, disposition, statesmanship, commandership and genius. In addition, he compares the Prophet Muhammad with other important figures in the world history. That’s why Celal Nuri’s ideas are important in enlightening the life of thoughts of recent period in a way
CELÂL NÛRÎ VE HÂTEMÜ’L-ENBİYÂ ADLI ESERİNE GÖRE HZ.MUHAMMED TASAVVURU